2003
DOI: 10.1046/j.1462-2920.2003.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse microbial communities inhabiting ferromanganese deposits in Lechuguilla and Spider Caves

Abstract: Lechuguilla Cave is an ancient, deep, oligotrophic subterranean environment that contains an abundance of low-density ferromanganese deposits, the origin of which is uncertain. To assess the possibility that biotic factors may be involved in the production of these deposits and to investigate the nature of the microbial community in these materials, we carried out culture-independent, small subunit ribosomal RNA (SSU rRNA) sequence-based studies from two sites and from manganese and iron enrichment cultures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
193
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(207 citation statements)
references
References 62 publications
10
193
2
1
Order By: Relevance
“…Such geomicrobial activity is thought to be indicated by the presence of corrosion residues: areas of fabric and mineralogical change in the bedrock, characterized by a color change and softening or powdering of the rock (Boston et al, 2001;Canaveras et al, 2001;Northup et al, 2003). While these residues do contain an observable microbial population, a mechanism of formation remains to be determined Northup et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Such geomicrobial activity is thought to be indicated by the presence of corrosion residues: areas of fabric and mineralogical change in the bedrock, characterized by a color change and softening or powdering of the rock (Boston et al, 2001;Canaveras et al, 2001;Northup et al, 2003). While these residues do contain an observable microbial population, a mechanism of formation remains to be determined Northup et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several clades within the Sphingomonadales were comprised of clones from both moonmilk sites, and were more closely related to each other than to previously retrieved environmental clones or cultured strains. Schabereiter-Gurtner et al (2004) retrieved similar alphaproteobacterial groups from cave-wall rock and Paleolithic paintings in Spain, and Northup et al (2003) found these genera from caves in New Mexico. Gurtner et al, 2002b;Schabereiter-Gurtner et al, 2002a;Schabereiter-Gurtner et al, 2004;Ikner et al, 2007).…”
Section: Summers Engel Et Almentioning
confidence: 98%
“…16S rRNA gene sequences were retrieved from moonmilk to evaluate the microbial diversity, which was expected to be high based on previous research of natural, cave-wall habitats (e.g., Northup et al, 2003;Chelius & Moore, 2004;Van de Kamp, 2004;Barton et al, 2007) and cave-walls with Paleolithic paintings or system having been anthropogenically impacted (e.g., Groth & Saiz-Jimenez, 1999; Schabereiterdella Foos percolating waters extractions during the summer (0.38 ± 0.14 mg/l Chl a), but nothing was detected from samples collected in the winter. Only moonmilk collected from the summer had detectable quantities of chlorophyll, with a composition of 0.14 ± 0.09 µg/l Chl a.…”
Section: Phylogenetic Analysis Of Microbial Communities From Moonmilkmentioning
confidence: 99%
See 2 more Smart Citations